1951
DOI: 10.1017/s0022029900006075
|View full text |Cite
|
Sign up to set email alerts
|

446. A note on the inhibition of an anaerobic sporeformer in Swiss-type cheese by a nisin-producing streptococcus

Abstract: Cheese of the Swiss (Emmenthaler, Gruyère, Danish-Swiss) type is popular on the continent of Europe and in America, but severe losses in ripening are caused by contamination with anaerobic sporeformers. Active gas production by the clostridia during ripening causes distension and spoiling of the cheese which becomes unmarketable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1956
1956
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(21 citation statements)
references
References 1 publication
0
20
0
1
Order By: Relevance
“…In 1944, Mattick and Hirsch succeeded in isolating the inhibitory substance (Mattick & Hirsch, 1944). Later, in the 1950s, the same research group successfully applied nisin in a Swiss-type cheese and in processed cheese to prevent gas defects caused by clostridia (Hawley, 1955;Hirsch, Grinsted, Chapman, & Mattick, 1951). The first commercial nisin preparation was available in 1957 (Delves-Broughton et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In 1944, Mattick and Hirsch succeeded in isolating the inhibitory substance (Mattick & Hirsch, 1944). Later, in the 1950s, the same research group successfully applied nisin in a Swiss-type cheese and in processed cheese to prevent gas defects caused by clostridia (Hawley, 1955;Hirsch, Grinsted, Chapman, & Mattick, 1951). The first commercial nisin preparation was available in 1957 (Delves-Broughton et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that nisin was very effective in the preservation of Swiss‐type and processed cheeses (Hirsch et al . ; Delves‐Broughton ). However, Kristoffersen and Chakraborty () stated that addition of nisin into cream dressing to a concentration in cottage cheese of 60–1200 IU/g (0.6–1.2 mg/g) decreased the shelf‐life of cottage cheese by 15–19%.…”
Section: Methods To Extend the Shelf‐life Of Cottage Cheesementioning
confidence: 99%
“…Yet another inhibitory effect of the lactic acid bacteria on the clostridia is by the production of nisin. Hirsch, Grinsted, Chapman & Mattick (1951) showed that the incorporation of a nisin-producing strain of Streptococcus lactis in the starter of Swiss-type cheese would prevent the cheese from blowing even when heavily inoculated with clostridia. Workers in France, Holland and Spain have amply confirmed this.…”
Section: (A) Antayonisnismentioning
confidence: 99%